Propofol-Remifentanil Combination for Management of Electroconvulsive Therapy in a Patient with Neuroleptic Malignant Syndrome - Modabber Arasteh; Shoaleh Shami; Karim Nasseri (Case Reports in Medicine)
Electroconvulsive therapy can be effective in severe or treatment resistant neuroleptic malignant syndrome patients. Anesthesia and use of muscle relaxant agents for electroconvulsive therapy in such patients may encounter anesthesiologists with specific challenges. This case report describes successful management of anesthesia in 28-year-old male patient undergoing eight electroconvulsive therapy sessions for treatment of neuroleptic malignant syndrome.